2021
DOI: 10.1038/s41467-021-22642-x
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Mfsd2b impairs thrombotic functions of platelets

Abstract: We recently discovered that Mfsd2b, which is the S1P exporter found in blood cells. Here, we report that Mfsd2b is critical for the release of all S1P species in both resting and activated platelets. We show that resting platelets store S1P in the cytoplasm. After activation, this S1P pool is delivered to the plasma membrane, where Mfsd2b is predominantly localized for export. Employing knockout mice of Mfsd2b, we reveal that platelets contribute a minor amount of plasma S1P. Nevertheless, Mfsd2b deletion in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Two proteins, Spns2 and Mfsd2b, have been validated as S1P transporters. Both transport proteins are members of the major facilitator superfamily (MFS) and extrude S1P in an ATP-independent fashion. , Genetic studies in mice revealed that Mfsd2b, which is expressed only in the erythroid lineage, is required for red blood cell release of S1P into plasma, while Spns2 is more widely expressed . Genetic studies in mice indicate that lymph S1P is primarily generated by Spns2-expressing endothelial cells lining the lymphatic vessels. While endothelial cells also line blood vessels, S1P transport by Mfsd2b is predominately responsible for maintaining plasma S1P concentrations. Maintenance of adequate lymph S1P is thought to be essential to promote lymphocyte egress from secondary lymphatic tissue into efferent lymph. ,,, Inhibition of Spns2 might be a pharmaceutically viable method to direct highly localized reductions in fluid S1P concentrations. , As such, our laboratories concentrated on developing chemical tools for inhibiting Spns2.…”
Section: Introductionmentioning
confidence: 99%
“…Two proteins, Spns2 and Mfsd2b, have been validated as S1P transporters. Both transport proteins are members of the major facilitator superfamily (MFS) and extrude S1P in an ATP-independent fashion. , Genetic studies in mice revealed that Mfsd2b, which is expressed only in the erythroid lineage, is required for red blood cell release of S1P into plasma, while Spns2 is more widely expressed . Genetic studies in mice indicate that lymph S1P is primarily generated by Spns2-expressing endothelial cells lining the lymphatic vessels. While endothelial cells also line blood vessels, S1P transport by Mfsd2b is predominately responsible for maintaining plasma S1P concentrations. Maintenance of adequate lymph S1P is thought to be essential to promote lymphocyte egress from secondary lymphatic tissue into efferent lymph. ,,, Inhibition of Spns2 might be a pharmaceutically viable method to direct highly localized reductions in fluid S1P concentrations. , As such, our laboratories concentrated on developing chemical tools for inhibiting Spns2.…”
Section: Introductionmentioning
confidence: 99%
“…We determined that Mfsd2b, which is expressed in blood cells, contributes approximately half of the plasma S1P (Vu et al, 2017). Among Mfsd2b-positive cells, erythrocytes and platelets have been shown to provide plasma S1P (Chandrakanthan et al, 2021;Nguyen et al, 2020;Tan et al, 2020). S1P is also released via Spns2, but the amount of plasma S1P contributed by Spns2 varies in different studies (Fukuhara et al, 2012;Mendoza et al, 2012;Nagahashi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…By selective deletion of SphK1 and SphK2, it has been established that endothelial and hematopoietic cells are the major sources of plasma S1P (Gazit et al, 2016). In line with these studies, it has been shown that Spns2 exports S1P from endothelial cells, whereas Mfsd2b exports S1P from erythrocytes and platelets (Fukuhara et al, 2012;Vu et al, 2017;Chandrakanthan et al, 2021). Although Spns2 deletion results in strong lymphopenia, vascular development and function are normal in Spns2 knockout mice (Mendoza et al, 2012).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…IL7R [202], S1PR1 [203], NFE2 [204], CCR2 [205], NLRP12 [206], PECAM1 [207], PIM1 [208], AP1S2 [209], ITK (IL2 inducible T cell kinase) [210], CCR4 [211], CX3CR1 [212], FOXO3 [213], CD28 [214], GPX1 [215], PRDX6 [216], LRRK2 [217], CCL5 [218], ETS1 [219], CCR3 [220], SELPLG (selectin P ligand) [221], VIM (vimentin) [222], CD1D [223], SIGLEC9 [224], TLR4 [225], FLNA (filamin A) [226], CCR7 [227], DPP4 [228], NLRC4 [229], TLR2 [230], DOCK2 [231], CD40LG [232], CD36 [233], MAPK1 [234], TGFBR2 [235], LTA4H [236], PECAM1 [237], VCAN (versican) [238], NPRL3 [239], CDC27 [240], PINK1 [241], TGFBI (transforming growth factor beta induced) [242], CR1 [243], AKT3 [244], STAT4 [245], CXCL10 [246], CRP (C-reactive protein) [247], IL17F [248], CD34 [249], BCL3 [250], TSLP (thymic stromal lymphopoietin) [251], CCL2 [252], F10 [253], STC1 [254], POSTN (periostin) [255], IL17A [256], SMOC2 [257], SFTPA2 [258], FAIM2 [259], LHX9 [260], HRG (histidine rich glycoprotein) [261] and CA9 [262] have been reported to be related to lung diseases, but these genes might be involved in the progression of COVID-19. SLC4A1 [263], CCR2 [264], FGL2 [265], CD84 [266], TLR4 [267], ITGB3 [268], TLR2 [267], CD36 [269], MFSD2B [270], PLXDC2 [271], KLF15 [272], C6 [273] and HRG (histidine rich glycoprotein) […”
Section: Discussionmentioning
confidence: 99%